Prevalence of Asymptomatic Bacteriuria and Antibiotic Susceptibility Patterns of Bacterial Isolates among Cancer Patients and Healthy Blood Donors at the University of Gondar Specialized Hospital - Abiye Tigabu; Worku Ferede; Gizeaddis Belay; Baye Gelaw (International Journal of Microbiology)
Background. Urinary tract infections are the common types of infections in the community and health care settings. Despite the widespread availability of antibiotics, urinary tract infection remains a worldwide therapeutic problem. It is a continuous and significant problem in cancer patients. Methods. A hospital-based comparative cross-sectional study was conducted on 240 study participants from January to June 2019. Sociodemographic data were collected by a predesigned questionnaire and midstream urine samples collected using simple random sampling technique by using clean, sterile plastic cups and then inoculated onto CLED agar plates and incubated at 37°C for 24 hours. Urine culture was considered significant bacteriuria when colony forming units ≥105/mL of voided urine and a single pure colony suspended in nutrient broth and then subcultured onto a blood agar plate and MacConkey agar plate, incubated at 37°C for 24 hours for identification. Identification was done by using standard microbiological methods. Modified Kirby–Bauer disk diffusion technique was applied for antimicrobial susceptibility testing in accordance with CLSI 2018 criteria. Data were entered, cleared, and checked using Epi Info version 7 and exported to SPSS version 20 for analysis. The results were displayed using tables and figures. p value <0.05 at 95% CI was considered as statistically significant. Results. The overall prevalence of asymptomatic bacteriuria in cancer patients was 23.3% while 6.7% in apparently healthy blood donors. E. coli (32.1%) was the commonest isolated uropathogenic bacteria followed by Klebsiella species (25.0%), S. aureus (21.4%), Enterococcus species (10.7%), Serratia species (7.1%), and Enterobacter aerogenes (3.6%) in cancer patients. In apparently healthy blood donors, E. coli, Klebsiella species, and S. aureus were isolated from 75%, 12.5%, and 12.5%, respectively. Most Gram-negative bacteria were more sensitive to ceftazidime, cefoxitin, nalidixic acid, nitrofurantoin, norfloxacin, ciprofloxacin, and tobramycin, whereas highly resistant to ampicillin, penicillin, tetracycline, and ceftazidime. S. aureus isolates were 100% susceptible to nitrofurantoin. Conclusions. This study showed a high prevalence of asymptomatic bacteriuria among cancer patients (23.3%) compared to apparently healthy blood donors (6.7%). E. coli was isolated predominately. Nitrofurantoin and ciprofloxacin should be used to treat asymptomatic bacteriuria in the study area.